2022
DOI: 10.1002/fsn3.2915
|View full text |Cite
|
Sign up to set email alerts
|

Applications of green technologies‐based approaches for food safety enhancement: A comprehensive review

Abstract: Food is the basic necessity for life that always motivated man for its preservation and making it available for an extended period. Food scientists always tried to preserve it with minimum deterioration in quality by employing and investigating innovative preservation techniques. The food sector always remained in search of eco‐friendly and sustainable solutions to tackle food safety challenges. Green technologies (ozone, pulsed electric field, ohmic heating, photosensitization, ultraviolet radiations, high‐pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Radioactivity, consumable covering, nitrogen oxides, ultraviolet, climate‐controlled storing, potassium permanganate, water, and sometimes perhaps viral proteins are just a few of the techniques that were researched to discover more efficient options to assure bacterial elimination on healthy produce (Mahajan et al, 2014; Islam et al, 2022). A few of the methods that have been studied to find more effective ways to ensure bacterial elimination on healthy produce include radioactivity, consumable covering, nitrogen oxides, ultraviolet, climate‐controlled storage, potassium permanganate, water, and occasionally perhaps viral proteins.…”
Section: Phage Research To Improve Food Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Radioactivity, consumable covering, nitrogen oxides, ultraviolet, climate‐controlled storing, potassium permanganate, water, and sometimes perhaps viral proteins are just a few of the techniques that were researched to discover more efficient options to assure bacterial elimination on healthy produce (Mahajan et al, 2014; Islam et al, 2022). A few of the methods that have been studied to find more effective ways to ensure bacterial elimination on healthy produce include radioactivity, consumable covering, nitrogen oxides, ultraviolet, climate‐controlled storage, potassium permanganate, water, and occasionally perhaps viral proteins.…”
Section: Phage Research To Improve Food Safetymentioning
confidence: 99%
“…There is a greater chance of contamination as a result. It has been shown that phages may be effectively utilized to lower microbial pollution on food products, hence enhancing food safety Antimicrobials are commonly present in a variety of products, including unpasteurized milk, poultry, cheeses, vegetables and fresh fruits (Greer, 2005;Islam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The ever-changing food industry requires students to update their knowledge system and to learn how to apply permanent theoretical knowledge to ever-changing practice [11]. This requires pluralistic lessons that keep abreast of the time.…”
Section: Optimize Teaching Effect In Line With Industrial Developmentmentioning
confidence: 99%
“…Food scientists have long attempted to preserve it with little quality loss by utilizing and researching novel preservation procedures. The food industry has always sought environmentally friendly and long-term solutions to food safety issues [2]. In this milieu, oilseed cakes are loaded with bioactive polyphenols and other antioxidants which play their role in the prevention and treatment of diseases [3].…”
Section: Introductionmentioning
confidence: 99%